2012
DOI: 10.1371/journal.pone.0043712
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar Protein Sorting Receptor in Giardia lamblia

Abstract: In Giardia, lysosome-like peripheral vacuoles (PVs) need to specifically coordinate their endosomal and lysosomal functions to be able to successfully perform endocytosis, protein degradation and protein delivery, but how cargo, ligands and molecular components generate specific routes to the PVs remains poorly understood. Recently, we found that delivering membrane Cathepsin C and the soluble acid phosphatase (AcPh) to the PVs is adaptin (AP1)-dependent. However, the receptor that links AcPh and AP1 was never… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 86 publications
(119 reference statements)
1
18
0
Order By: Relevance
“…These trophozoites were used as hosts for the expression of transgenic genes and as wild-type controls. The GlVps open reading frames were amplified from genomic DNA using the primers reported [14]. The GlVPS35 was amplified using the 35F (CATTGGATCCATGGCTTTCCAGACCAAAGTAGACC) and 35R (CATT GCATGC GTTTCCGAGGAAGATCTCCATCCTCT) cloned into the tetracycline-inducible vector pINDG-HA modified by introduction of the HA epitope at the C-terminus to generate the p GlVPS-HA vector [26].…”
Section: 0 Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These trophozoites were used as hosts for the expression of transgenic genes and as wild-type controls. The GlVps open reading frames were amplified from genomic DNA using the primers reported [14]. The GlVPS35 was amplified using the 35F (CATTGGATCCATGGCTTTCCAGACCAAAGTAGACC) and 35R (CATT GCATGC GTTTCCGAGGAAGATCTCCATCCTCT) cloned into the tetracycline-inducible vector pINDG-HA modified by introduction of the HA epitope at the C-terminus to generate the p GlVPS-HA vector [26].…”
Section: 0 Materials and Methodsmentioning
confidence: 99%
“…Thus, although Giardia lacks distinct endosomes and lysosomes, it contains peripheral vacuoles (PVs), which perform the role of endosome and lysosome simultaneously [1113]. We recently showed that soluble hydrolase acid phosphatase (AcPh) is delivered to the PVs by the concerted action of the giardial receptor Vps (GlVps) and adaptor protein 1 (AP-1) [14] but whether GlVps is later recycled to the ER is still unknown.…”
Section: 0 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AP-1µ also binds the vacuolar receptor Vps, and its knockdown by dsRNA induces degradation of Vps; this is specific to AP-1, as AP-2µ does not bind Vps [51]. Knockdown of AP-1µ also results in mis-localization of two peripheral vacuole proteins [50].…”
Section: Functional Homology In Trafficking Machinery Between Divermentioning
confidence: 99%
“…Encystation-specific vesicles for the secretion of cyst wall materials constitute a separate class that have been characterized using proteomics. The elaborate glycan-dependent quality-control on unfolded proteins observed in general in eukaryotes is replaced by a novel process in G. intestinalis consisting of the up-regulation of only about 30 genes [36,37]. Specialized endocytotic vesicles, the peripheral vesicles, internalize bulk fluid phase material principally on the dorsal side opposite the attachment disc of the organism.…”
Section: Organelles and Vesiclesmentioning
confidence: 99%